2016
DOI: 10.1055/s-0041-111502
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic ultrasound-guided hepaticogastrostomy using a 6-F cystotome and 12-cm covered metal stent

Abstract: Background and study aims: An iincreasing number of reports describe endoscopic ultrasound-guided hepaticogastrostomy for malignant biliary obstruction in patients with endoscopic retrograde cholangiopancreatography failure. However, this procedure has not yet been standardized; as a result, the rate of adverse events, including bile leakage and stent migration, is relatively high. Here, we report our experience with four cases of endoscopic ultrasound-guided hepaticogastrostomy performed according to our inst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…The cystotome as an accessory has been described for drainage of pancreatic pseudocysts internally via gastric or duodenal routes and that is where it is still most commonly used 9 . Recently, its use has been extended to endoscopic ultrasound (EUS)-guided pancreatic cyst/necrotic collections drainage, as well as EUS-guided bile duct drainage 10 . For this purpose, routinely, 10 Fr cystotome assemblies are employed to create fistulas between pancreatic cysts and the gastric wall.…”
Section: Discussionmentioning
confidence: 99%
“…The cystotome as an accessory has been described for drainage of pancreatic pseudocysts internally via gastric or duodenal routes and that is where it is still most commonly used 9 . Recently, its use has been extended to endoscopic ultrasound (EUS)-guided pancreatic cyst/necrotic collections drainage, as well as EUS-guided bile duct drainage 10 . For this purpose, routinely, 10 Fr cystotome assemblies are employed to create fistulas between pancreatic cysts and the gastric wall.…”
Section: Discussionmentioning
confidence: 99%
“…For hepaticogastrostomy, long stents may decrease the risk of stent migration. Indeed, a stent length ≥3 cm in the intraluminal portion was shown to be associated with a lower risk of stent migration in a retrospective study including 51 patients [6] and a small study including 4 patients reported no migration when ≥10 cm stents (total length) were used [4]. Choosing a stent with a large diameter is also important to decrease the risk of stent dysfunction due to granulation tissue in the hepatic side of the stent, although the ideal diameter is not well established.…”
Section: Discussionmentioning
confidence: 98%
“…Bile leak is the most frequent adverse event, although other early and late complications can occur. Early complications include cholangitis, bleeding, stent misplacement, and bile leaks [4]. Dilation of the tract before stent insertion is recommended to decrease the risk of bile leaks since it avoids frequent device exchange and decreases procedural time.…”
Section: Discussionmentioning
confidence: 99%
“…Reports have presented a case in which a 6-cm covered metallic stent migrated with a fatal outcome and a case in which an 8-cm covered metallic stent migrated, necessitating surgical treatment [ 3 , 4 ]. Moreover, a recent report described a significantly shorter median stent patency duration in patients who underwent EUS-HGS with an intragastric stent < 3 cm in length than in those who underwent EUS-HGS with an intragastric stent ≥ 3 cm in length [ 5 ]; therefore, we believe that stents measuring 10 cm or longer should be used [ 6 ].…”
Section: Discussionmentioning
confidence: 99%